The case for microbiome stewardship: what it is and how to get there - Mallory J. Choudoir; Suzanne L. Ishaq; Robert G. Beiko; Diego S. Silva; Emma Allen-Vercoe; Kieran C. O’Doherty (mSystems)
ABSTRACT Microbiomes are essential for human, animal, plant, and ecosystem health. Despite widespread recognition of the importance of microbiomes, there is little attention paid to monitoring and safeguarding microbial ecologies on policy levels. We observe that microbiomes are deteriorating owing to practices at societal levels such as pesticide use in agriculture, air and water pollution, and overuse of antibiotics. Potential policy on these issues would cross multiple domains such as public health, environmental protection, and agriculture. We propose microbiome stewardship as a foundational concept that can act across policy domains to facilitate healthy microbiomes for human and ecosystem health. We examine challenges to be addressed and steps to take toward developing meaningful microbiome stewardship.